2019
DOI: 10.1111/fcp.12444
|View full text |Cite
|
Sign up to set email alerts
|

Major bleeding with antithrombotic agents: a 2012–2015 study using the French nationwide Health Insurance database linked to emergency department records within five areas – rationale and design of SACHA study

Abstract: Bleeding represents the most recognized and feared complications of antithrombotic drugs including oral anticoagulants. Previous studies showed inconsistent results on the safety profile. Among explanations, bleeding definition could vary and classification bias exists related to the lack of medical evaluation. To quantify the risk of major haemorrhagic event and event‐free survival associated with antithrombotic drugs (vitamin K antagonist [VKA], non‐VKA anticoagulant [NOAC], antiplatelet agent, parenteral an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…The study design has previously been reported [ 18 ]. Briefly, a prospective population-based cohort study was set up linking the French Health Insurance Database (SNIIRAM) to data from all emergency departments located within five well-defined areas around five large French cities (Angers, Brest, Grenoble, Nantes and Rennes).…”
Section: Methodsmentioning
confidence: 99%
“…The study design has previously been reported [ 18 ]. Briefly, a prospective population-based cohort study was set up linking the French Health Insurance Database (SNIIRAM) to data from all emergency departments located within five well-defined areas around five large French cities (Angers, Brest, Grenoble, Nantes and Rennes).…”
Section: Methodsmentioning
confidence: 99%
“…The SACHA study is a French prospective population-based cohort on the incidence and outcome of major bleeding among patients treated with antithrombotics (parenteral or oral anticoagulant, or antiplatelet agent). The detailed methods have already been published[ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we chose to focus on certain specific ADRs that concerned ICD10 codes related to dermatological effects (L27.0, L51.1, L51.2), anaphylactic shock (T88.2, T88.6), nephropathy (N14.1, N14.2, N17), hepatic impairment (K71), neuropathy (G62.0) and interstitial lung disease (J70.2, J70.3, J70.4), and either the association of ICD10 code K71 with codes Y40 to Y59/T88.7 or the association of code N17 with the same codes (Appendix Table A1). This choice was based on the results of a previous study performed in 2009 in Rennes evaluating queries on various ICD10 codes to the PMSI database to identify serious ADRs 16 and on the existence of another study 17,18 (see Appendix 1).…”
Section: Methodsmentioning
confidence: 99%
“…What this study adds Table A1). This choice was based on the results of a previous study performed in 2009 in Rennes evaluating queries on various ICD10 codes to the PMSI database to identify serious ADRs 16 and on the existence of another study 17,18 (see Cases were analysed by the RPVC. Drug causality was assessed using the official French method.…”
mentioning
confidence: 99%